Biofortification: Effect of Iodine Fortified Food in the Healthy Population, Double-Arm Nutritional Study - Baldassano, Sara; Di Gaudio, Francesca; Sabatino, Leo; Caldarella, Rosalia; De Pasquale, Claudio; Di Rosa, Luigi; Nuzzo, Domenico; Picone, Pasquale; Vasto, Sonya (Frontiers in Nutrition, 2022)
It is estimated that a third of the world's population lives in areas where iodine (I) is scarce and its deficiency is responsible for many related disorders such as goiter, reproductive failure, hearing loss, growth impairment, cretinism, and numerous kinds of brain injury. Mineral deficiencies can be overcome via dietary diversification and mineral supplementation. An alternative or even complementary way is represented by the intake of bio-fortified foods, which can tackle this lack of micronutrients. In this short-term double-arm nutritional intervention study a cohort of ten people was supplemented with curly endive leaf biofortified with iodine (I) and ten people with curly endive without biofortification (Intervention Study on Iodine Biofortification Vegetables ( Nutri-I-Food - Full Text View - ClinicalTrials.gov). After 12 days and the effects on whole body homeostasis and specifically on iodine, glucose, lipid, hepatic, iron metabolism was investigated. Blood samples were obtained at baseline and after 12 days of supplementation with curly endive and compared to controls. Hematochemical and urinary parameters were analysed at baseline and after 12 days. The results showed that short term I curly endive intervention, did not affect the whole body homeostasis in healthy people and revealed increase in I concentration in urine samples, increase in vitamin D, calcium and Potassium concentration in blood samples only in the biofortified cohort respect to controls. The study suggests that short term consumption of I curly endive crops is safe and could positively impact on body health.